The Effect of Subjective Loss in Financial Risk Taking and Negative Emotion - Mei, Dongmei; He, Shasha; Li, Liman Man Wai; Zhu, Yiyi (Frontiers in Psychology, 2021)
The current research examined the influence of subjective loss on financial risk-taking tendency and negative emotional experience through inducing the experience of subjective loss in auction scenarios. In Study 1, we found that the subjective loss experience (compared to no-loss experience) in an auction scenario induced greater financial risk propensity, especially in gambling, greater negative emotion, and greater decision regret. In addition, we found that the subjective loss experience induced stronger negative emotion but less risk propensity in investment than the actual loss experience did, but these two types of loss did not yield a difference in risk propensity in gambling in Study 2. These results implicate that subjective loss is a distinct experience from no-loss and actual loss experiences, which is reflected by the degree of associated emotional experience and subsequent risk-taking propensity. The current research highlights the complex psychological processes of the experience of loss in decision-making contexts.